2019
DOI: 10.2174/1389201020666190612160631
|View full text |Cite
|
Sign up to set email alerts
|

A Weighted Ensemble Model for Prediction of Infectious Diseases

Abstract: Background: The ensemble building is a common method to improve the performance of the model in case of regression as well as classification. Objective: In this paper we propose a weighted average ensemble model to predict the number of incidence for infectious diseases like typhoid and compare it with applied models for prediction. Methods: The Monthly data of dengue and typhoid cases from 2014 to 2017 were taken from integrated diseases surveillance programme, Government of India. The data was processed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…An increasing number of the relevant scholars have studied the prediction of infectious diseases and published many papers in the past two decades [ 6 , 7 , 8 ]. To provide a comprehensive review of the prediction of infectious diseases, some scholars have proposed systematic reviews, including Racloz et al [ 9 ], Huppert and Katriel [ 10 ], Christaki [ 11 ], Alessa and Faezipour [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of the relevant scholars have studied the prediction of infectious diseases and published many papers in the past two decades [ 6 , 7 , 8 ]. To provide a comprehensive review of the prediction of infectious diseases, some scholars have proposed systematic reviews, including Racloz et al [ 9 ], Huppert and Katriel [ 10 ], Christaki [ 11 ], Alessa and Faezipour [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…When we evaluated the studies regarding the types of models used in the predictions, we observed that the vast majority of authors investigated moving average models (27), such as the Autoregressive Integrated Moving Average (ARIMA) (17,23,29,35,41,43,46,56,(61)(62)(63), Seasonal Autoregressive Integrated Moving Average (SARIMA) (55,(63)(64)(65)(66), Autoregressive Integrated Moving Average with Explanatory Variable (ARIMAX) (67). Several works have also presented a wide variety of models using artificial neural networks, mainly the LSTM (59,(68)(69)(70).…”
Section: Arboviruses (Counts) Predictionmentioning
confidence: 99%
“…But models using backpropagation neural networks (BPNN), GANN networks (60), Elman Recurrent Neural Network Levenberg Marquardt Algorithm (ERMN/LMA) (22), and Deep feed-forward neural networks (28) were also investigated. Although neural networks have been extensively explored, in many studies, the authors did not explain the type of network they were investigating (23,45,46,61,66,71,72).…”
Section: Arboviruses (Counts) Predictionmentioning
confidence: 99%
“…Shashvat et al. Shashvat et al. (2019) predicted the incidence of infectious diseases like typhoid using an ensemble of models like mean squared error (MSE), root mean squared error (RMSE), and mean absolute error (MAE).…”
Section: Related Workmentioning
confidence: 99%